Biological Characterization, Mechanistic Investigation and Structure‐Activity Relationships of Chemically Stable TLR2 Antagonists. (3rd June 2020) - Bermudez, Marcel; Grabowski, Maria; Murgueitio, Manuela S.; Tiemann, Markus; Varga, Péter; Rudolf, Thomas; Wolber, Gerhard; Weindl, Günther; Rademann, Jörg
Abstract: Toll‐like receptors (TLRs) build the first barrier in the innate immune response and therefore represent promising targets for the modulation of inflammatory processes. Recently, the pyrogallol‐containing TLR2 antagonists CU‐CPT22 and MMG‐11 were reported; however, their 1, 2, 3‐triphenol motif renders them highly susceptible to oxidation and excludes them from use in extended experiments under aerobic conditions. Therefore, we have developed a set of novel TLR2 antagonists (1 –9 ) based on the systematic variation of substructures, linker elements, and the hydrogen‐bonding pattern of the pyrogallol precursors by using chemically robust building blocks. The novel series of chemically stable and synthetically accessible TLR2 antagonists (1 –9 ) was pharmacologically characterized, and the potential binding modes of the active compounds were evaluated structurally. Our results provide new insights into structure‐activity relationships and allow rationalization of structural binding characteristics. Moreover, they support the hypothesis that this class of TLR ligands bind solely to TLR2 and do not directly interact with TLR1 or TLR6 of the functional heterodimer. The most active compound from this series (6 ), is chemically stable, nontoxic, TLR2‐selective, and shows a similar activity with regard to the pyrogallol starting points, thus indicating the variability of the hydrogen bonding pattern. Abstract : Undegraded : The 1, 2, 3‐triphenol motif of known TLR2 antagonists is highly susceptible to oxidation and excludes them from use in extended experiments under aerobic conditions. Herein, we report a rationally developed series of novel TLR modulators resulting in compound 6, a novel, chemically stable, nontoxic, TLR2‐selective antagonist.